Indução de anticorpos neutralizantes contra herpesvírus bovino e vírus da diarreia viral bovina por vacinas comerciais e vacina experimental associada com diferentes adjuvantes - Dotto, Evelyn Kaus (2020)
Bovine alphaherpesvirus 1 (BoHV-1) and Bovine viral diarrhea virus (BVDV) are important pathogens of cattle whose losses may be prevented by vaccination. This study evaluated the serological response induced by commercial vaccines and by an experimental vaccine associated with different adjuvants. For this, groups of seronegative heifers were immunized twice (30 days apart) with nine commercial vaccines and tested for virus neutralizing (VN) antibodies to the respective viruses 30 days after the second vaccine dose (D60). For the adjuvant test, inactivated BoHV-1 and BVDV-1 antigens were combined with six different adjuvants and submitted to the same immunization and serology protocol. Seven out of nine commercial vaccines induced VN antibodies to BoHV-1 at day D60, but only three induced titers considered protective (≥ 16). The frequency of seroconversion among the vaccines varied from 0% (0/10 animals) to 100% (10/10) and the geometric mean titers (GMT) ranged from 0 to 43. The frequency of seroconversion in protective titers was 100%, 37,5% and 25%, respectively. Only four vaccines induced neutralizing titers to BVDV-1 and three to BVDV-2 at D60. The frequency of seroconversion to BVDV among the vaccines varied from 0% (0/10 animals) to 100% (10/10) and the geometric mean titers (GMT) ranged from 0 to 202. Only three vaccines conferred titers compatible with protection (>60). The frequency of seroconversion in protective titers was 55,5%, 42,8% and 12,5% for BVDV-1, respectively. All experimental vaccine formulations induced VN titers against BoHV-1 at D60 (frequency of seroconversion varied from 0% to 100% and GMT= varied from 2 to 20) and four induced protective titers. The frequency of seroconversion in protective titers was 100%, 33,3%, 30% and 20%, respectively. On the other hand, none of the experimental vaccines was able to induce VN antibodies to BVDV at D60. Under the conditions of the present study, most commercial vaccines induced unsatisfactory VN response against the tested viruses, most noticeably to BVDV. Among the experimental vaccines, the adjuvant Emulsigen - DL90 (DDA) was more effective to induce VN antibodies against BoHV-1, but not to BVDV. These results indicate the need for reformulation of vaccine composition and/or immunization protocols as to achieve more consistent serological response to BoHV-1 and, especially, to BVDV.